Health promoter, advocate, legitimiser - the many roles of WHO guidelines: a qualitative study - Zhicheng Wang; Quinn Grundy; Lisa Parker; Lisa Bero (BMC, 2019)
Abstract Background Properly implemented evidence-based clinical and public health guidelines can improve patient outcomes. WHO has been a major contributor to guideline development, publishing more than 250 guidelines on various topics since 2008. However, well-developed guidelines can only be effective if they are adequately and appropriately implemented. Herein, we aimed to explore whether and how WHO guidelines are implemented in local contexts to inform the success of future guideline implementation. Methods Seventeen interviews were carried out between March 2018 and December 2018 with WHO guideline developers, headquarter staff, and regional and country office staff. Participants were purposely sampled from a variety of WHO guidelines and snowball sampling was used to identify regional and country office staff. The deidentified transcripts were analysed through three phases of coding, using grounded theory as the analytic approach. Results WHO guidelines played a variety of roles in the work of WHO at all levels. WHO officers and local government officials used WHO guidelines to influence health policy. We categorised the uses of guidelines as (1) directly changing policy, (2) justifying policy change, (3) engaging stakeholders, (4) being guarantors of legitimacy, (5) being advocacy tools, and (6) intertwining with WHO's various roles. Participants refuted the perception of the guidelines as mere lists of technical recommendations that needed to be implemented in different contexts. We found that the existence, quality and credibility, rather than the content of the guidelines, are the keys to health policy change initiatives in different local contexts. Conclusions Used as a guarantor of legitimacy by policy-makers, WHO guidelines can be better positioned to influence health policy and practice change. Understanding the various roles of guidelines can help WHO developers package guidelines to optimise their effective implementation. Ethics This project was conducted with ethics approval from The University of Sydney (Project number: 2017/723) and WHO (Protocol ID: 00001).